Characterization of white grub (Melolonthidae; Coleoptera) in salak plantation based on morphology and protein banding pattern - KRISNANDARI TITIK MARYATI; SUGIYARTO SUGIYARTO (Smujo International, 2009)
Abstract. Maryati KT, Sugiyarto. 2010. Characterization of white grub (Melolonthidae; Coleoptera) in salak plantation based on morphology and protein banding pattern. Nusantara Bioscience 1: 72-77. This research aims to find out the white grub (Melolonthidae; Coleoptera) variability based on the morphological characteristic and protein banding pattern found in